ANALISIS PAPARAN GAS KARBON MONOKSIDA (CO) DAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI (APD) TERHADAP KELUHAN PERNAFASAN PADA PEKERJA WELDING DI PT. X KOTA BATAM - Jamal, Jamal; Fauzi, Asnil; Sundaru, Agung (Jurnal Liga Ilmu Serantau, 2026)
Respiratory complaints are a health problem that can be experienced by construction workers, especially welding workers, primarily due to exposure to Carbon Monoxide gas. This study aims to analyze the relationship between carbon monoxide (CO) gas exposure and respiratory Personal Protective Equipment (PPE) usage behavior with respiratory complaints among welding workers. This research is an analytical observational study with a cross-sectional design conducted at PT. X in Batam City, Riau Islands from February to July 2024. The entire population of 35 welding workers was taken as a sample through the total sampling method. Based on the research results, the chi-square statistical test shows a p-value of 0.030 < α = 0.05 for the relationship between CO gas exposure and respiratory complaints, so Ho is rejected and Ha is accepted. This means that there is a significant relationship between exposure to carbon monoxide (CO) gas and respiratory complaints in workers. Furthermore, the chi-square statistical test for the relationship between PPE usage behavior and respiratory complaints resulted in a p-value of 0.046 < α = 0.05, so Ho is rejected and Ha is accepted, which means there is a significant relationship. The results of this study show that 74% of workers were exposed to CO gas above the threshold limit value (25 ppm), 60% used respiratory PPE, and 63% experienced respiratory complaints. Suggestions for the company include evaluating working hours, periodic health monitoring, improving ventilation, optimizing PPE usage, and further research on lung function disorders using spirometry.